Delayed Infliximab Treatment Affects the Outcomes of Patients With Crohn's Disease During the COVID-19 Epidemic in China: A Propensity Score-Matched Analysis - Li, Yong; Chen, Lulu; Chen, Shuijiao; Liu, Xiaowei (Frontiers in Medicine, 2022)
Background The coronavirus disease 2019 (COVID-19) has swept the world and led to delays in the treatment of Crohn's disease patients treated with biologics. This study aims to investigate the risk factors for delayed treatment during the epidemic and to observe the short- and long-term influences of such delays among them to provide some reference on treatments. Methods This study retrospectively enrolled patients diagnosed with Crohn’s disease who received infliximab treatment between January 23, 2020 and April 30, 2020. Univariate and multivariate logistic regression were used to analyze the risk factors for delayed treatment. Propensity score matching was utilized to compare the effects of delayed treatment on the short- and long-term outcomes. Result Our cohort identified a total of 53 patients with a delay rate of 71.7%. Of these patients, 38 were in the delayed group, and 15 were in the non-delayed group. Logistic regression analysis showed that the baseline levels of C-reactive protein were an influence factor for delaying treatment (OR = 0.967, 95% CI = 0.935-1.000, p= 0.047). Regarding short-term effects, the delayed group had a lower decrease in the Crohn’s Disease Activity Index than the non-delayed group [-17.3 (-29.0, 79.9) vs. -43.3 (-92.7, -9.7), p = 0.038] and significantly higher long-term readmission rates (33.3% vs. 0%, p = 0.014). Conclusion Delayed infliximab treatment could affect the short- and long-term outcomes in patients with Crohn’s disease. Our study suggested that the regulated course of treatment with biological agents should be performed effectively and that education should be enhanced to minimize delays in treatment.